2017
DOI: 10.1002/biof.1389
|View full text |Cite
|
Sign up to set email alerts
|

Ageratum conyzoides L. inhibits 5‐alpha‐reductase gene expression in human prostate cells and reduces symptoms of benign prostatic hypertrophy in otherwise healthy men in a double blind randomized placebo controlled clinical study

Abstract: A double-blind, randomized, placebo-controlled clinical trial assessed the efficacy and safety of Ageratum conyzoides in treating benign prostatic hypertrophy (BPH). In this study, 109 men with medically diagnosed BPH, aged 41-76 years, were administered the investigational product, A. conyzoides extract at a dose of 250 mg/d or placebo, q.d. for 12 weeks. The primary outcome measures were the International Prostate Symptom Score (IPSS), daily urinary frequency and safety evaluations. The secondary outcome mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…[7,28] Further it was reported that the ethyl alcohol extract of the aerial parts of Ageratum conyzoides L. was effective in reducing the expression of mRNA coding for 5α-reductase type 2 and 1 in in-vitro human prostate epithelial cell. [32] Together this study provided sufficient information regarding the beneficial effect of Ageratum conyzoides L. plant extract on the testosterone induced BPH model.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…[7,28] Further it was reported that the ethyl alcohol extract of the aerial parts of Ageratum conyzoides L. was effective in reducing the expression of mRNA coding for 5α-reductase type 2 and 1 in in-vitro human prostate epithelial cell. [32] Together this study provided sufficient information regarding the beneficial effect of Ageratum conyzoides L. plant extract on the testosterone induced BPH model.…”
Section: Discussionmentioning
confidence: 74%
“…[29][30][31] Recent studies also show that ethylalcohol extract of the aerial parts of Ageratum conyzoides L. was effective in reducing the expression of mRNA coding for 5α-reductase type 2 and 1 in in-vitro human prostate epithelial cell. [32] In the prostate cell, testosterone can be converted to dihydrotestosterone (DHT) by the enzyme 5α-reductase. DHT has 5 times higher affinity for the androgen receptor in the nucleus than testosterone and excessive production of DHT with increasing aging may play a critical role in the pathogenesis of BPH.…”
Section: Discussionmentioning
confidence: 99%
“…In some African countries, the plant is useful in conventional medicine due to its anti-asthmatic, antispasmodic, and hemostatic properties [ 72 , 73 ]. The ACE contains numerous phytochemical compounds that may have different therapeutic activities such as antioxidant, antibacterial, antimicrobial, anticancer, etc., either from crude or tissue-specific fractions (Table 2 ) [ 8 , 9 , 74 ]. It has been also used to cure urinary and prostate-related issues in traditional practices for a long time.…”
Section: Evaluation Of Traditional Medicinal Uses By Molecular Toolsmentioning
confidence: 99%
“…The extract showed a significantly reduced human 5-α-reductase mRNA level in prostate epithelial cells. Thus, A. conyzoides could potentially be used for the treatment of BPH by decreasing the enzyme activity of 5-α-reductase [ 74 ], and can be employed after purifying the active component from ACE with subsequent clinical studies.…”
Section: Evaluation Of Traditional Medicinal Uses By Molecular Toolsmentioning
confidence: 99%
“…As men age, enzymes such as aromatase and 5-alpha reductase increase in activity ( Martin and Touaibia, 2020 ). These enzymes aid in the conversion of androgen hormones to oestrogenic and dihydrotestosterone (DHT), respectively ( Detering et al, 2017 , Mohamad et al, 2018 ). As a result, the levels of testosterone decrease, while the levels of oestrogen and DHT increase ( Benrick et al, 2017 , Li et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%